2019
DOI: 10.1007/s13201-019-0924-x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cu(II) using three low-cost adsorbents and prediction of adsorption using artificial neural networks

Abstract: Adsorption of copper using groundnut seed cake power, sesame seed cake powder and coconut cake powders as bioadsorbents was optimized at a pH of 5, temperature of 40 °C, initial metal concentration of 10 mg/L, contact time of 30 min and adsorbent dosage 0.75 g for groundnut seed cake powder and 1.0 g of sesame seed cake powder and coconut cake powder. From the results of kinetic studies, it was concluded that the adsorption process followed pseudo-second-order kinetics. Langmuir adsorption isotherm fit perfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Thus, the Freundlich isotherm is a better isotherm to describe the adsorption of Ni(II) and Cu(II) ions onto Delonix regia leaves, whereas the Langmuir isotherm is better fitted to describe adsorption onto the pods. Kumar et al (2019) reported that the sorption of Cu(II) ions onto groundnut seed cake, sesame seed cake and coconut cake powders fit perfectly to the Langmuir isotherm with a Q 0 value ranging from 3.608 to 3.703 mg g −1 . Likewise, Saeed et al (2005a) reported that the biosorption of Cu(II) ions perfectly fit the Langmuir adsorption isotherm model.…”
Section: Initial Adsorbate Concentration and Isotherm Experimentsmentioning
confidence: 90%
See 2 more Smart Citations
“…Thus, the Freundlich isotherm is a better isotherm to describe the adsorption of Ni(II) and Cu(II) ions onto Delonix regia leaves, whereas the Langmuir isotherm is better fitted to describe adsorption onto the pods. Kumar et al (2019) reported that the sorption of Cu(II) ions onto groundnut seed cake, sesame seed cake and coconut cake powders fit perfectly to the Langmuir isotherm with a Q 0 value ranging from 3.608 to 3.703 mg g −1 . Likewise, Saeed et al (2005a) reported that the biosorption of Cu(II) ions perfectly fit the Langmuir adsorption isotherm model.…”
Section: Initial Adsorbate Concentration and Isotherm Experimentsmentioning
confidence: 90%
“…Alatabe (2018) reported 120 min as the optimum sorption time for Cu(II) ions onto activated carbon from Cane papyrus. However, 30 min was the optimum contact time reported by Kumar et al (2019) for the removal of Cu(II) ions using groundnut seed cake powder, sesame seed cake powder and coconut cake powder. The kinetic modelling of data showed that the process was well fitted to the pseudo-second-order kinetic model.…”
Section: Contact Timementioning
confidence: 93%
See 1 more Smart Citation
“…A high number of approaches have been adapted and practiced to ensure the environmental safety against copper, the most widespread methods being used are: chemical precipitation, chelation/complexation, ion exchange, membrane ltration, ultraltration, reverse osmosis, electrodialysis, otation, among others; all these methods have disadvantages as expensive chemical requirements, energetic costs, sludge disposal issues, among others. [9][10][11] Due to this, the processes involving chemical adsorption have become very important alternatives, owing to their cheap cost effectiveness and the high-quality of the produced treated effluents. 12,13 Among available adsorbents, metal oxides, including ferric oxides, manganese oxides, aluminum oxides, magnesium oxides and cerium oxides, are classied as promising surfaces for heavy metal removal from aqueous systems.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these, there are a number of effluents and emissions in the atmosphere. Mining activities also add to this problem particularly dusting and particulate matter thus, pollution is a gift of industrial civilization [4][5][6][7] . Among the many other low cost absorbents identified, chitosan has the highest absorption capacity for several metals.…”
Section: Introductionmentioning
confidence: 99%